ANALISIS STRUKTUR ALUR KUMPULAN CERPEN ROBOHNYA SURAU KAMI KARYA AA. NAVIS - Jupon, Rara Marselina (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2020)
Literature is the work of human creations to express their experiences through language, both orally and in writing that can cause a sense of beauty and can thrill the readers, besides that literature is also born of a cultural situation, not because of cultural emptiness, literature was born to realize the culture itself in its own way. A collection of short stories "The Fall of Our Surau" by AA. Navis contains ten short stories. This study is useful to find out what plot is used by the writer in a collection of short stories and determine the type of flow and structure of the grooves in each of the short stories. Results of the analysis of a collection of short stories by AA. Navis, it can be concluded that the collection of short stories by AA. Navis has four fronts, consisting of Pride Children, Advice, Helm Caps and Birth awaits. Whereas the short story that uses a backward flow consists of the collapse of our Surau, the Coming and Departing, the Final Fraction, the Wind from the Mountain, the Helper and From Time to Time.